2011
DOI: 10.1161/hypertensionaha.110.169193
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Impairs Endothelial Progenitor Cell Number and Function In Vitro and In Vivo

Abstract: Abstract-Endothelial progenitor cells (EPCs) contribute to endothelial regeneration. Angiotensin II (Ang II) through Ang II type 1 receptor (AT 1 -R) activation plays an important role in vascular damage. The effect of Ang II on EPCs and the involved molecular mechanisms are incompletely understood. Stimulation with Ang II decreased the number of cultured human early outgrowth EPCs, which express both AT 1 -R and Ang II type 2 receptor, mediated through AT 1 -R activation and induction of oxidative stress. Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
80
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 51 publications
7
80
0
5
Order By: Relevance
“…However, because the angiogenic potential of progenitor cells does not entirely depend on true EPCs, 3 this question seems more academic than of clinical interest. The in vitro results (see Figure 1 of the article by Endtmann et al 4 ) show that non-EPC MNC types are also affected and emphasize the importance of studying the immunomodulatory role of Ang II in vascular disease, a field of research that is gaining attention. In all likelihood, an interplay between EPCs and inflammatory cells exists that is of utmost importance for the vasoprotective effects of pharmacological renin-angiotensin system modulation.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…However, because the angiogenic potential of progenitor cells does not entirely depend on true EPCs, 3 this question seems more academic than of clinical interest. The in vitro results (see Figure 1 of the article by Endtmann et al 4 ) show that non-EPC MNC types are also affected and emphasize the importance of studying the immunomodulatory role of Ang II in vascular disease, a field of research that is gaining attention. In all likelihood, an interplay between EPCs and inflammatory cells exists that is of utmost importance for the vasoprotective effects of pharmacological renin-angiotensin system modulation.…”
mentioning
confidence: 93%
“…2,7 The chronic, deleterious effects on cultured EPCs depend on ROS release, and accumulation of damage to macromolecules, in particular to DNA, might be a necessary, timeconsuming interlude between ROS release and induction of apoptosis or senescence. In addition, Endtmann et al 4 observed that ROS production in EPCs is increasing during the first 48 hours of Ang II treatment. Perhaps the induction of deleterious Ang II effects in EPCs requires a high degree of ROS production, for example, to circumvent the protective effect of antioxidant pathways.…”
mentioning
confidence: 99%
See 3 more Smart Citations